2015
DOI: 10.3126/jcmsn.v11i1.13318
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fine needle aspiration cytology of cervical lymphadenopathy in Bir Hospital

Abstract: Background & Objectives: To correlate FNAC of cervical lymphadenopathy with the histopathology.Materials and Methods: Prospective study on 67 patients with cervical lymphadenopathy at the ENT Department, Bir Hospital, from January 2013 to July 2014. Patients were subjected to both FNAC and histopathology.Results: Thirty cases (44.8%) were females and 37 cases (55.2%) were males. Tuberculosis was most common disease in 30(44.80%) patients. Sensitivity, specificity, and diagnostic accuracy of FNAC to diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
2
2
1
Order By: Relevance
“…3 Khadka et al reported, sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy for granulomatous lymphadenopathies were 90.0%, 98.0%, 90.0%, 98.0% and 97.01% respectively. 10 In this study 9 (13.43%) cases, cytological diagnosis was not correlating with histopathological diagnosis but FNAC and histopathology correlated in 86.57% cases. This concluded that FNAC is very simple and accurate technique and can distinguish tubercular lymphadenitis from reactive and granulomatous lymphadenitis in majority of cases.…”
Section: Resultscontrasting
confidence: 53%
“…3 Khadka et al reported, sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy for granulomatous lymphadenopathies were 90.0%, 98.0%, 90.0%, 98.0% and 97.01% respectively. 10 In this study 9 (13.43%) cases, cytological diagnosis was not correlating with histopathological diagnosis but FNAC and histopathology correlated in 86.57% cases. This concluded that FNAC is very simple and accurate technique and can distinguish tubercular lymphadenitis from reactive and granulomatous lymphadenitis in majority of cases.…”
Section: Resultscontrasting
confidence: 53%
“…A declining trend in cases has been observed after 30 years of age. This corroborates with other studies conducted by other studies [8]. The high incidence of tuberculosis may be explained by the fact of low socioeconomic condition, poorhygiene and lack of awareness in the region.…”
Section: Most Of the Cases Occurred Between 20-29 Years Of Agesupporting
confidence: 92%
“…Males were affected morethan females. These findings correlate with study by Shakera N Baji and coworker [8]. The incidence of reactive lymph node enlargement fell steadily the 5th decade onwards and malignant lesions being most common.…”
Section: Most Of the Cases Occurred Between 20-29 Years Of Agesupporting
confidence: 90%
“…Lymphadenopathy is one of the commonest clinical presentation in outpatient clinic of many hospitals and quite worrying to patients. 1 Enlarged lymph node can be the first clinical presentation of metastatic disease in patient suffering from non-hematological malignancies. 2 The utility of Fine Needle Aspiration Cytology (FNAC) is well established in diagnosis of metastatic lymph nodes, new onset or recurrence.…”
Section: Introductionmentioning
confidence: 99%